Digital Twins for Education: A Literature Review - Bachmann, João Eduardo Cosentino; Silveira, Ismar Frango; Martins, Valeria Farinazzo (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
The evolution of Virtual Reality (VR) to Digital Twins (DT) represents a significant advancement in the field of immersive and interactive technologies, particularly when aiming to establish a connection between the physical and synthetically generated worlds. This connection provides conditions for simulation, prevention, and optimization of processes and systems in the real environment. The importance of this topic is based on various reasons. Opportunities are envisioned to apply DTs in several industrial sectors, like Education, especially in the areas of STEAM (Science, Technology, Engineering, Arts, and Mathematics). These applications can reduce costs and maximize innovation opportunities in the teaching-learning processes, supporting the testing of scenarios and strategies in a safe virtual environment that correlates with real-world implementation. Thus, this paper presents a literature review on the applications of DT in Education, offering a contemporary panorama and pointing out some directions for future research.